Pengaruh Iklim Organisasi dan Motivasi Kerja terhadap Kinerja Guru Sekolah Menengah Atas di Kabupaten Bandung - Istiqomah, Istiqomah (Advances In Social Humanities Research, 2024)
This study aims to determine the effect of organizational climate and work motivation on the performance of high school teachers (SMA) in Bandung Regency, using quantitative descriptive research methods. The statistical test used is the path analysis test. The population in this study amounted to 358 high school teachers in Bandung Regency, the sampling technique in this study used Proportional Straified Random Sampling, as many as 79 teachers. The results showed that (1) Organizational Climate has a significant effect on the Performance of Senior High School Teachers (SMA) in Bandung Regency. Organizational climate individually has a significant influence on teacher performance, the contribution of organizational climate to the performance of high school teachers (SMA) in Bandung Regency is 68.8%. (2) Work motivation has a significant effect on the performance of high school teachers (SMA) in Bandung Regency. Individual work motivation has a significant effect on teacher performance, the contribution of work motivation to the performance of high school teachers (SMA) in Bandung Regency is 79.5% (3) Organizational Climate and Work Motivation have a significant effect on the Performance of Senior High School Teachers (SMA) in Bandung Regency. Organizational climate and work motivation simultaneously and individually have a significant influence on teacher performance, the contribution of work motivation to the performance of high school teachers (SMA) in Bandung regency is 86.5%.